Implementation Of Face-To-Face Online Learning System Based On Audio Video, Presentation And Chat Using The Moodle E-Learning Platform - Dedy Arisandi; Seniman; Nababan, Erna Budhiarti; Opim Salim Sitompul (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Currently, the implementation of teaching and learning at SMP Negeri 1 Binjai Kwala Begumit was done in the classroom alternately. However, with the current condition of pandemic covid-19, the learning process no longer carried out fully in schools. The school has not been using information technology in the form of e-learning applications in the teaching and learning process. The school has difficulty in recording the existing teaching and learning process: assignments, exams, assessments, and other activities. Therefore the use of e-learning applications is now very much needed. With existing school facilities, such as internet facilities and the ICT teachers, training in developing and implementing e-learning for teaching staff become the best alternative so that learning process can be done properly.